x^2-4√2+6=0 completing the square
Answers
Answered by
1
x2−4∗2–√+6=0x2−4∗2+6=0
=>x2−22–√x−22–√x+8−2=0=>x2−22x−22x+8−2=0
=>x∗(x−22–√)−22–√(x−22–√)−2=0=>x∗(x−22)−22(x−22)−2=0
=>(x−22–√)2−(2–√)2=0=>(x−22)2−(2)2=0
=>(x−22–√)2=(2–√)2=>(x−22)2=(2)2
=>(x−22–√)=±2–√=>(x−22)=±2
Assuming+2–√,=>(x−22–√)=2–√=>x=32–√Assuming+2,=>(x−22)=2=>x=32
Assuming−2–√,=>(x−22–√)=−2–√=>x=2–√
=>x2−22–√x−22–√x+8−2=0=>x2−22x−22x+8−2=0
=>x∗(x−22–√)−22–√(x−22–√)−2=0=>x∗(x−22)−22(x−22)−2=0
=>(x−22–√)2−(2–√)2=0=>(x−22)2−(2)2=0
=>(x−22–√)2=(2–√)2=>(x−22)2=(2)2
=>(x−22–√)=±2–√=>(x−22)=±2
Assuming+2–√,=>(x−22–√)=2–√=>x=32–√Assuming+2,=>(x−22)=2=>x=32
Assuming−2–√,=>(x−22–√)=−2–√=>x=2–√
Similar questions